5‐Fluorouracil‐Loaded Sodium Alginate/Konjac Glucomannan Interacted with Attapulgite as a Potential Drug Delivery System. Issue 22 (9th June 2022) - Yang, Zhe; Fang, Jahui; Tian, Dating; Hu, Sheng
Abstract: 5‐FU loaded sodium alginate / konjac glucomannan (SA/KGM) and sodium alginate / konjac glucomannan / attapulgite (SA/KGM/ATP) microbeads were fabricated by an injection method. FTIR, SEM, XRD, TGA, DSC, and EDS were used to characterize these fabricated microbeads. Besides, encapsulation efficiency, swelling and in vitro drug release studies were also carried out. The results show that the addition of ATP can make the encapsulation efficiency of the model drug reach 76.58±0.91 %, and significantly reduce the burst release of 5‐FU within 300 minutes. Moreover, four common kinetic models were used to assessed the in vitro release kinetics and the results supported Ritger‐Peppas models, also indicating the mechanism of drug transport was controlled by Fickian diffusion. The results suggest that the prepared SA/KGM/ATP microbeads could potentially to be used in drug delivery system. Abstract : This study an injection gelation method was used to fabricate 5‐FU loaded microbeads. We found that drug molecules are stored in molecular level in the complex network formed by cross‐linking of attapulgite and natural high molecular polymers, which can improve the encapsulation efficiency of drug molecules and control the release of drug molecules.